Penggunaan Low Level Laser dalam Dermatologi Kosmetik - Mutia Fadhila Sy; Jusuf, Nelva Karmila (Cermin Dunia Kedokteran, 2024)
Low level laser therapy (LLLT) is used in almost all areas of modern medicine, including cosmetic dermatology. LLLT has been beneficial for the treatment of wrinkles, acne vulgaris, hypertrophic scars, hair loss, cellulite, and burns. LLLT can reduce UV damage both as a treatment and as a prophylaxis. In pigmentation disorders such as vitiligo, LLLT can increase pigmentation by stimulating melanocyte proliferation and reducing depigmentation. The non-invasive nature and near absence of side effects of LLLT encourage further research in cosmetic dermatology.